Oral health knowledge and oral hygiene practices of pre-school teachers in a selected region of Kathmandu city - Dikshit, Parajeeta; Limbu, Senchhema; Gupta, Sujaya (Indian Journal of Child Health, 2022)
Background: Dental caries and periodontal diseases are the most common oral health problems seen globally. Schools provides an ideal environment for all forms of education, including oral health and teachers can be instrumental in imparting it. The teachers, therefore, need to be well versed in the knowledge regarding oral health as well as practice good oral hygiene measures to teach the children. Objectives: The objective of this study is to assess pre-school teachers’ oral health knowledge and oral hygiene practices in a selected region of Kathmandu city. Methodology: An observational, descriptive cross-sectional study was conducted on preschoolteachers in a selected region of Kathmandu city. The teachers of pre-school level completed a self-administered structured questionnaire on knowledge of oral health and oral hygiene practices Result: The pre-school teachers had more knowledge about dental caries than about periodontal diseases. Overall, scores of school teacher’s (n=95) oral health knowledge were inadequate (54.7%) but the oral hygiene practices (69.5%) were found to be good. Conclusion: The pre-school teachers had inadequate oral health knowledge but good oral hygiene practices. This shows a need for training and motivation of pre-school teachers’ regardingthe oral health education and promotion through school-based programs.